Neuroprotective effects of Ac.YVAD.cmk on experimental spinal cord injury in rats - (:unkn) unknown (ELSEVIER SCIENCE INC, 2008)
Background: Apoptosis as a cell death mechanism is important in numerous diseases, including traumatic SCI. We evaluated the neuroprotective effects of Ac.YVAD.cmk and functional outcomes in a rat SCI model. Methods: Thirty rats were randomized into 3 groups of 10: sham-operated, trauma only, and trauma plus Ac.YVAD.cmk treatment. Trauma was produced in the thoracic region by a weight-drop technique. Group 3 rats received Ac.YVAD.cmk (1 mg/kg, ip) 1 minute after trauma. The rats were killed at 24 hours and 5 days after injury. Efficacy was evaluated with light microscopy and TUNEL staining. Functional outcomes were assessed with the inclined plane technique and a modified version of the Tarlov grading system. Results: At 24 hours postinjury, the respective mean number of apoptotic cells in groups 1, 2, and 3 were 0, 5.26 +/- 0.19, and 0.97 +/- 0.15. Microscopic examination of group 2 tissues showed widespread hemorrhage, edema, necrosis, and polymorphic nuclear leukocyte infiltration and vascular thrombi. Group 3 tissues revealed similar features, but cavitation and demyelination were less prominent than those in group 2 samples at this period. At 5 days postinjury, the respective mean 5 inclined plane angles in groups 1, 2, and 3 were 61.5 +/- 2.09, 42.00 +/- 2.74, and 52.5 +/- 1.77. Motor grading of animals revealed a similar trend. These differences were statistically significant (P < .05). Conclusions: Ac.YVAD.cmk inhibited postraumatic apoptosis in a rat SCI model. This may provide the basis for development of new therapeutic strategies for the treatment of SCI. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Ac.YVAD.cmk; apoptosis; caspases; SCI; secondary damage; CASPASE INHIBITORS; CELL-DEATH; NEURONAL APOPTOSIS; CEREBRAL-ISCHEMIA; FAMILY PROTEASES; BRAIN-INJURY; INTERLEUKIN-1-BETA; ICE; IDENTIFICATION; EXPRESSION